(untitled) (Research, Society and Development, 2022)
The present work intends to report the experience of nursing students in extension actions with the aim of promoting health education for adolescents in a school environment. This is a descriptive study of the experience report type about extensionist experiences of health education addressed by nursing students in the fourth semester of a university in the northern region of the state of Ceará, applied to high school students from a state school of the same municipal location. The themes of Drug Use Prevention, Sexuality and Pregnancy Prevention, Suicide and Bullying Prevention and Group Living were addressed. The themes were addressed through dynamic activities such as board games and “Truth” or “Myth” signs. All school students participated in the actions at different times, totaling an audience of 400 adolescents. Regarding the perception of health with an adolescent public, several doubts were identified regarding the proposed themes, mainly related to sexuality. The dynamics proved to be fundamental for the setting with the moment, allowing the insertion of the team within the students’ space, in addition to the analysis of their previous knowledge, their main difficulties. Therefore, we can observe how important the role of the school is in the personal formation of adolescents and how much it is necessary to work on social issues, since the school is the place where they spend most of their time, forming bonds and sharing their experiences.